(untitled) (Altre Modernità, 2020)
In this article I problematize the notions of disability and Bildungsroman in Guadalupe Nettel’s novel El cuerpo en que nací. First, I analyze the way in which the body of the protagonist, inscribed under the paradigm of correction and rehabilitation, finds in writing an artistic and literary alternative that defamiliarizes the representation of the ’disabled’ body and discredits the imperative of aesthetic disqualification. In this way, I propose to detail the relationship that the protagonist sponsors between her body and writing in order to confront and highlight the discourse of ophthalmolocentrism and capacitism. Secondly, I read the novel against the grain of the Bildungsroman tradition to see it as an anti-training narrative that focuses on the celebratory and political forms of bodily difference and the destabilization of its dominant protocols of representation.